Bipolar Disorder: Evaluation of a Psychoeducational Program under a Behavior Analysis focus (Brazilian Journal of Behavioral and Cognitive Therapy, 2013)
Psychoeducation is one of the strategies that must be used in the treatment of bipolar disorder patients and has demonstrated effectiveness in promoting medication compliance. The aim of this study was to evaluate the effectiveness of a psychoeducation program applied to nine patients diagnosed with bipolar disorder receiving treatment in a public hospital. For evaluation, scales of depression (Hamilton), mania (Young) and Quality of Life (WHOQOL) were used. Sixteen sessions of group care were performed and the results showed significant reduction in mania evaluation after the intervention after a six month follow-up and an improvement in the field “Physical” of the Quality of Life scale, evaluated before and after the intervention. Moreover, the high frequency of patients with mild depression and reports of family conflicts as antecedents of this episode showed the necessity of intervention with the family and a focus on social skills training.
Keywords: Psychoeducation; Group; Bipolar Affective Disorder; Behavior Analysis